2017
DOI: 10.1002/celc.201701168
|View full text |Cite
|
Sign up to set email alerts
|

Metal Loading Effect on the Activity of Co3O4/N‐Doped Reduced Graphene Oxide Nanocomposites as Bifunctional Oxygen Reduction/Evolution Catalysts

Abstract: The development of effective and stable reversible oxygen electrodes is of upmost importance for bringing regenerative energy storage and conversion systems to a commercial reality. However, realization of such electrodes is motivated by low activity and instability of the current electrocatalysts working for both water splitting and oxygen reduction. Herein, we report a series of Co3O4/graphene‐based catalysts with different Co mass loadings prepared by using a facile one‐step hydrothermal route. N‐doped redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…Kumar et al used a simple hydrothermal approach to create a composite of cobalt oxide and nitrogen-doped reduced graphene oxide (Co 3 O 4 / NrGO). 570,571 Raman spectroscopy revealed peaks for the sp 3 carbon at 1180 cm À1 , the disordered carbon D band at 1350 cm À1 , the amorphous sp 2 carbon at 1540 cm À1 , the E 2g mode at 1590 cm À1 , and the intercalation in graphite at 1620 cm À1 . The XPS analysis confirmed that C, N, O, and Co were present in the composite.…”
Section: Supercapacitorsmentioning
confidence: 99%
“…Kumar et al used a simple hydrothermal approach to create a composite of cobalt oxide and nitrogen-doped reduced graphene oxide (Co 3 O 4 / NrGO). 570,571 Raman spectroscopy revealed peaks for the sp 3 carbon at 1180 cm À1 , the disordered carbon D band at 1350 cm À1 , the amorphous sp 2 carbon at 1540 cm À1 , the E 2g mode at 1590 cm À1 , and the intercalation in graphite at 1620 cm À1 . The XPS analysis confirmed that C, N, O, and Co were present in the composite.…”
Section: Supercapacitorsmentioning
confidence: 99%
“…Kumar et al fabricated a cobalt oxide/nitrogen-doped reduced graphene oxide composite (Co 3 O 4 /NRGO) via a simple hydrothermal method. 84 Raman spectroscopy exhibited a peak at 1180 cm −1 , corresponding to the sp 3 carbon, a peak at 1350 cm −1 , corresponding to the D band of disordered carbon, a peak at 1540 cm −1 , corresponding to the amorphous sp 2 carbon, G band at 1590 cm −1 , corresponding to the E 2g mode, and D band at 1620 cm −1 , corresponding to the intercalation in graphite. The XPS study confirmed that the composite contained C, N, O, and Co.…”
Section: Doping-induced Modified Graphene Compositesmentioning
confidence: 99%
“…The cobalt oxide morphology can be easily tuned by controlling the precipitation of the corresponding precursors through varying the pH value governed by urea concentration [27]. The oxygen functionalities grafted onto GO surface (e.g., −COOH, −OH) act as ligands enabling the nucleation and growth of the cobalt oxide precursor, which leads to a strong affinity of the as-grown mesoporous cobalt carbonate and the GO surface [1,18]. Besides, during the hydrothermal treatment, GO is chemically reduced to rGO.…”
Section: Physical Featuresmentioning
confidence: 99%
“…The binding energy of Co 2p3/2 and Co 2p1/2 photopeaks at 780.0 and 794.5 eV with energy difference of 15.2 eV indicates the co-existence of Co 2+ and Co 3+ species on the surface of the material [28]. Herein, the Co 2p spectra were processed and decomposed using two reference spectra corresponding to commercial Co3O4 (red curve) and CoO (green curve) materials [18,29]. For all the samples, the obtained spectra can be expressed as a linear combination of spectra recorded for these two reference materials, confirming therefore that the materials are composed of hybrids Co3O4-CoO.…”
Section: Physical Featuresmentioning
confidence: 99%